Association of early changes of circulating cancer stem-like cells with survival among patients with metastatic breast cancer. (July 2022) - Chang, Pei-Hung; Lee, Chun-Hui; Wu, Tyler Min-Hsien; Yeh, Kun-Yun; Wang, Hung-Ming; Huang, Wen-Kuan; Chan, Sheng-Chieh; Chou, Wen-Chi; Kuan, Feng-Che; Kuo, Hsuan-Chih; Kuo, Yung-Chia; Hu, Ching-Chih; et al.
Background: This study aimed to investigate the role of circulating tumor cells (CTCs) and circulating cancer stem-like cells (cCSCs) before and after one cycle of chemotherapy and assessed the effects of early changes in CTCs and cCSCs on the outcomes of patients with metastatic breast cancer. Methods: Patients with stage IV invasive ductal carcinoma of the breast who received first-line chemotherapy between April 2014 and January 2016 were enrolled. CTCs and cCSCs were measured before the first cycle of chemotherapy (baseline) and on day 21, before the second cycle of chemotherapy commenced; a negative selection strategy and flow cytometry protocol were employed. Results: CTC and cCSC counts declined in 68.8 and 45.5% of patients, respectively. Declines in CTCs and cCSCs following the first chemotherapy cycle were associated with superior chemotherapy responses, longer progression-free survival (PFS), and longer overall survival (OS). An early decline in cCSCs remained an independent prognostic indicator for OS and PFS in multivariate analysis. Conclusions: A cCSC decline after one cycle of chemotherapy for metastatic breast cancer is predictive of a superior chemotherapy response and longer PFS and OS, implying that cCSC dynamic monitoring may be helpful in early prediction of treatment response and prognosis.